Analysis of the Assortability of Ophthalmologists Using a Therapy as Part of Routine Medical Care for Patients with Inflammatory Eye Diseases - I. V. Vorobyeva; M. A. Frolov; Yu. B. Slonimskiy (Oftalʹmologiâ)
The problem of diagnosis and treatment of inflammatory eye diseases takes a leading place in Russia and in the world, but the most important thing is the correct choice of treatment methods. Purpose of the work: collection and analysis of data on doctors’ preferences under prescribing therapy in patients with inflammatory eye pathology in routine clinical practice. As a result, 5960 clinical cases from 47 Russian cities were analyzed. This article compiles data from October to November 2020. 151 medical researchers were taken part in the participation of the recruitment. Doctors made different diagnoses for referring patients, but significantly more often diagnosis H10.3 was detected — 17.99 % (in 1072 patients). Ophthalmologists preferred to prescribe the following combination of drugs: 1 — antibacterial local, 2 — local antiseptics, 3 — non-steroidal anti-inflammatory local, a combination (antibiotic and glucocorticosteroid), antiallergic in the form of drops of local action. The choice of drugs for inflammatory eye disease is determined by their high efficiency of use for a given disease: antibiotic Signicef® (levofloxacin 0,5 %), nonsteroidal anti-inflammatory drug Broxinac® (bromphenac 0,09 %), fixed combination Kombinil® (ciprofloxacin 0,3 % + dexamethasone 0,1 %), Visallergol® (olopatadine 0,2 %) in the form of topical eye drops.